Differential overexpression of SERPINA3 in human prion diseases. Issue 1 (December 2017) - Vanni, S.; Moda, F.; Zattoni, M.; Bistaffa, E.; De Cecco, E.; Rossi, M.; Giaccone, G.; Tagliavini, F.; Haïk, S.; Deslys, J.; Zanusso, G.; Ironside, J.; et al.
Abstract Prion diseases are fatal neurodegenerative disorders with sporadic, genetic or acquired etiologies. The molecular alterations leading to the onset and the spreading of these diseases are still unknown. In a previous work we identified a five-gene signature able to distinguish intracranially BSE-infected macaques from healthy ones, withSERPINA3 showing the most prominent dysregulation. We analyzed 128 suitable frontal cortex samples, from prion-affected patients (variant Creutzfeldt-Jakob disease (vCJD) n = 20, iatrogenic CJD (iCJD) n = 11, sporadic CJD (sCJD) n = 23, familial CJD (gCJD) n = 17, fatal familial insomnia (FFI) n = 9, Gerstmann–Sträussler–Scheinker syndrome (GSS)) n = 4), patients with Alzheimer disease (AD, n = 14) and age-matched controls (n = 30). Real Time-quantitative PCR was performed forSERPINA3 transcript, andACTB, RPL19, GAPDH andB2M were used as reference genes. We reportSERPINA3 to be strongly up-regulated in the brain of all human prion diseases, with only a mild up-regulation in AD. We show that this striking up-regulation, both at the mRNA and at the protein level, is present in all types of human prion diseases analyzed, although to a different extent for each specific disorder. Our data suggest thatSERPINA3 may be involved in the pathogenesis and the progression of prion diseases, representing a valid tool for distinguishing different forms of these disorders in humans.